A recurrent mosaic mutation of SMO, encoding the hedgehog signal transducer Smoothened, is the major cause of Curry-Jones syndrome - Twigg, S; Wilkie, A; Hufnagel, R; Miller, K; Zhou, Y; McGowan, S; Taylor, J; Craft, J; Taylor, J; Santoro, S; Huang, T; Hopkin, R; et al. (Cell Press, 2016)
Curry-Jones syndrome (CJS) is a multisystem disorder characterized by patchy skin lesions, polysyndactyly, diverse cerebral malformations, unicoronal craniosynostosis, iris colobomas, microphthalmia, and intestinal malrotation with myofibromas or hamartomas. Cerebellar medulloblastoma has been described in a single affected individual; in another, biopsy of skin lesions showed features of trichoblastoma. The combination of asymmetric clinical features, patchy skin manifestations and neoplastic association previously led to the suggestion that this could be a mosaic condition, possibly involving Hedgehog (Hh) signaling. Here we show that CJS is caused by recurrent somatic mosaicism for a nonsynonymous variant in SMO (c.1234C>T; p.Leu412Phe), encoding Smoothened (SMO), a G protein-coupled receptor that transduces Hh signaling. We identified eight mutation-proven individuals (including two previously unreported), with highly similar phenotypes, in whom we demonstrate varying amounts of the mutant allele in different tissues. We present detailed findings from magnetic resonance brain imaging in three mutation-positive cases. Somatic mutations of SMO that result in constitutive activation have been described in several tumors, including medulloblastoma, ameloblastoma and basal cell carcinoma. Strikingly, the most common of these mutations is the identical nonsynonymous variant encoding p.Leu412Phe. Furthermore, this substitution has been shown to activate SMO in the absence of Hh signaling, providing an explanation for tumor development in CJS. This raises therapeutic possibilities using recently generated Hh pathway inhibitors. In summary, our work uncovers the major genetic cause of CJS and illustrates strategies for gene discovery in the context of low-level tissue-specific somatic mosaicism.